2013
DOI: 10.1016/j.bjoms.2013.09.002
|View full text |Cite
|
Sign up to set email alerts
|

A 3D anthropometric analysis of the orolabial region in Chinese young adults

Abstract: The orolabial region frequently undergoes significant changes following trauma, orthognathic surgery or orthodontics. Ethnicity, age and gender specific normative data are needed during the planning phase before surgical interventions in this region. In 2008 the British Journal of Oral and Maxillofacial Surgery published anthropometric lip measurements of Chinese children; however such reference data for Chinese young adults are currently unavailable. Therefore this cross-sectional study using 3-D facial photo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
24
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(32 citation statements)
references
References 13 publications
7
24
1
Order By: Relevance
“…Studies on the analysis of the face morphology of Asian populations showed mouth width values and upper lip vermillion height greater than those found by this present study [10,13,18], while the studies on Black and White Americans observed mouth width values more similar to those of the Brazilians and Peruvians [11,17]. The vestibular shift of maxillary incisors and canines can affect the upper and lower vermilion areas of the lips [20], therefore the assessment of the upper anterior teeth shapes is important to the study of lips stereophotogrammetry, especially when comparing different ethnicities, which may present different trends of dental positioning [21].…”
Section: Discussioncontrasting
confidence: 54%
See 1 more Smart Citation
“…Studies on the analysis of the face morphology of Asian populations showed mouth width values and upper lip vermillion height greater than those found by this present study [10,13,18], while the studies on Black and White Americans observed mouth width values more similar to those of the Brazilians and Peruvians [11,17]. The vestibular shift of maxillary incisors and canines can affect the upper and lower vermilion areas of the lips [20], therefore the assessment of the upper anterior teeth shapes is important to the study of lips stereophotogrammetry, especially when comparing different ethnicities, which may present different trends of dental positioning [21].…”
Section: Discussioncontrasting
confidence: 54%
“…The authors used a new method of 3D anthropometric measurement to delineate the Chinese nose shape to contribute with the plastic surgeons [12]. Yasas et al verified the orolabial region of Chinese females and males through 3D images aiming to standardize the lip morphology and enable an adequate planning and better prognosis prior to either orthognathic surgery, lip reconstruction, or orthodontics [13].…”
Section: Ngeowmentioning
confidence: 99%
“…An anthropometric analysis scheme developed for qualifying facial norms [Jayaratne et al 2013a; Jayaratne et al 2013b; Jayaratne et al 2014b; Jayaratne et al 2014c] was used with suitable modifications to suit the current project. Landmarks were identified by a single investigator (YSNJ) with significant experience in digital craniofacial anthropometry.…”
Section: Methodsmentioning
confidence: 99%
“…5 The standards of nasal parameters can be used as a standard for comparing treatment outcomes, treatment planning in orthodontics, and nasal surgeries. 6 Nasal norms can be measured by direct clinical measurement (morphometric), lateral cephalograms, 7 two-dimensional 8 and three-dimensional (3D) 6 photographs, 3D white light scanners, 9 and 3D laser scans. 10 The rationale of performing of this study is to have population-specific values of nasal length, which could assist us in orthodontic and orthognathic surgery treatment planning of the Saudi population.…”
Section: Introductionmentioning
confidence: 99%